Kontroling Pembelajaran Biologi Berbasis Cinta di SMK Kesehatan Athallah Putra Palembang - Helvi Oktalia; Ahmad Zainuri; Arni Arni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the application of biology learning control based on the value of love at SMK Kesehatan Athallah Putra Palembang. The concept of control applied not only focuses on formal supervision but also emphasizes a humanistic guidance approach, which includes attention, emotional support, and motivation for students. This research uses a descriptive qualitative method with data collection techniques such as observation, interviews, and documentation. The results show that the implementation of love-based control creates a harmonious, interactive, and comfortable learning environment. Teachers act not only as supervisors but also as mentors who play a role in fostering positive character and enhancing student learning motivation. With this approach, better relationships between teachers and students are formed, encouraging students to be more active in the learning process. Love-based control is proven to be effective in improving the quality of biology learning at SMK Kesehatan Athallah Putra, while also instilling positive humanitarian values in the school environment. This study shows that the application of control focused on love can have a positive impact on the quality of education.